2020
DOI: 10.1167/tvst.9.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Bioptic Telescope Use in Naturalistic Driving by People with Visual Impairment

Abstract: Purpose:The purpose of this study was to investigate the telescope use behaviors in natural daily driving of people with reduced visual acuity licensed to drive with a bioptic (a small spectacle-mounted telescope). Methods:A large dataset (477 hours) of naturalistic driving was collected from 19 bioptic drivers (visual acuity 20/60 to 20/160 without the telescope). To reduce the data volume, a multiloss 50-layer deep residual neural network (ResNet-50) was used to detect potential bioptic telescope use events.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…In a recent naturalistic driving study, 477 hours of driving data were analyzed from recordings of daily driving of 19 bioptic drivers. 8 The median duration (1.4 seconds) for each bioptic use event in this habitual, on-road driving was very similar to the median duration of each bioptic use event for the current drivers in the current study (1.66 seconds). The similarity in the duration of bioptic uses between the two studies suggests that the bioptic use behaviors of the current bioptic drivers in our driving simulator were representative of real-world bioptic-use behaviors.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In a recent naturalistic driving study, 477 hours of driving data were analyzed from recordings of daily driving of 19 bioptic drivers. 8 The median duration (1.4 seconds) for each bioptic use event in this habitual, on-road driving was very similar to the median duration of each bioptic use event for the current drivers in the current study (1.66 seconds). The similarity in the duration of bioptic uses between the two studies suggests that the bioptic use behaviors of the current bioptic drivers in our driving simulator were representative of real-world bioptic-use behaviors.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, we suggest that the ring scotoma of a monocular bioptic telescope is not a major safety concern, especially given that bioptic telescopes are typically used for only a very small proportion of total driving time. 7,8 However, detection rates were lower and reaction times longer for pedestrian appearances that overlapped with the bioptic use suggesting that the detection task was more difficult in this dual task situation. In sum, the ring scotoma seems to have little impact on pedestrian hazard detection in binocular viewing when the fellow eye can compensate.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In reality, there is an ethical barrier preventing researchers from studying driving safety in naturalistic settings in drivers with visual acuity far below the licensure thresholds. Considering the very low rate of use of bioptic telescopes in their driving, 6 investigating this unique population of drivers can help us to better understand the role of vision in driving in general, that is, bioptic drivers can serve as a cohort for researchers to ethically and legally study the role of vision in driving in natural real-world environments.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent naturalistic driving study on a group of visually impaired drivers with bioptic telescope, we found that the median time spent looking through the telescope was only 1.4% of the total driving time. 6 In other words, the subjects were driving with a low level of visual acuity most of the time. This finding raises obvious questions about whether driving with impaired central vision and only occasional, brief use of the telescope is hazardous.…”
Section: Introductionmentioning
confidence: 99%